2021
DOI: 10.1002/anie.202101992
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of Nanographenes

Abstract: Suitably decorated small aromatic systems can organize stacked structures that display interesting properties arising from their unique morphologies. Although nanographenes produced by top‐down methods have graphitic domains and can in principle be applied for such supramolecular systems, to our knowledge, no such example has been reported thus far. This is partly because of their limited solubility in organic solvents and partly because of their wide lateral size distribution. To realize nanographene‐based su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Chiroptical properties of PG1 were investigated in aqueous solutions at room temperature (25 °C) in the presence of different anions; the circular dichroism (CD) spectra are shown in Figure a. Obvious Cotton effects were observed with the first positive peak around 370 nm and the second negative peak around 310 nm in the wavelength range of 290–430 nm, suggesting that the polymer main chain adopts a preferred right-handed helix conformation. , Surprisingly, PG1 showed nearly identical Cotton effects at 25 °C, irrelevant to the presence of either salt-in or salt-out anions, although these anions exhibit large differences for T cp . Since the chirality of PPAs is dependent mainly on the ordered orientation of OEG pendants around the backbone through cooperative H bonding in the neighboring units, these unvaried CD spectra indicate that, at room temperature, added anions can only interact differently with OEG moieties (to afford different thermoresponsiveness) but not with the inner part of the polymer chains to exert influence on the backbone chirality.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Chiroptical properties of PG1 were investigated in aqueous solutions at room temperature (25 °C) in the presence of different anions; the circular dichroism (CD) spectra are shown in Figure a. Obvious Cotton effects were observed with the first positive peak around 370 nm and the second negative peak around 310 nm in the wavelength range of 290–430 nm, suggesting that the polymer main chain adopts a preferred right-handed helix conformation. , Surprisingly, PG1 showed nearly identical Cotton effects at 25 °C, irrelevant to the presence of either salt-in or salt-out anions, although these anions exhibit large differences for T cp . Since the chirality of PPAs is dependent mainly on the ordered orientation of OEG pendants around the backbone through cooperative H bonding in the neighboring units, these unvaried CD spectra indicate that, at room temperature, added anions can only interact differently with OEG moieties (to afford different thermoresponsiveness) but not with the inner part of the polymer chains to exert influence on the backbone chirality.…”
Section: Results and Discussionmentioning
confidence: 99%
“…NGs are potential candidates for EC materials due to their chemical stability in the oxidation state and absorption band covering the visible region due to their large π‐conjugated systems. Their optical properties can be regulated by postsynthetic modifications [17–22] . We showed that electronic interactions between the edge and installed substituents can influence the electronic and optical properties of NGs [22] .…”
Section: Figurementioning
confidence: 92%
“…Among the graphene family, we have employed NGs with tens of nanometers. Our studies demonstrated that the integration of NGs with organic and supramolecular chemistry can widen the scope of their applications [29–33] . Therefore, we describe our research on the development of NG‐based functional materials by the postsynthetic modification.…”
Section: Introductionmentioning
confidence: 97%
“…Our studies demonstrated that the integration of NGs with organic and supramolecular chemistry can widen the scope of their applications. [29][30][31][32][33] Therefore, we describe our research on the development of NG-based functional materials by the postsynthetic modification. We hope that the results of our research will contribute to the development of the chemistry of 2D species.…”
Section: Introductionmentioning
confidence: 99%